The Effect of Gamma Rays in Some Optical and Physical Properties of the Material (PVA) Dissolved in Distilled Water - Saad Khalid Rahi (Journal of Global Pharma Technology, 2019)
This research includes a study of some optical properties of (PVA) which is dissolved in distilled water before and after irradiation by (γ-ray) the Radiation was done using Co60 source at the rate of 1.25 Mev and the irradiation process was carried out in the Institute and Hospital Radiation and Nuclear Medicine at dose of (8000 rad) with average radiation (500 rad / min) for (16 min). The study of optical properties had included measurement of absorbance, transmission, index of refraction has been measured for all concentration before and after irradiation, as well as the reflectivity, molar refractivity, and absorption coefficient has been measured. The results shown that the value of absorbance, index of refraction, are increases as the solution concentration increased before and after irradiation, but the value of transmission, absorption coefficient and reflectivity are decreased when the solution concentration increased before and after irradiation. All measurements are calculated at a constant temperature approximately to (25oC). The reason for the change at value of properties may be due to cross linking of polymer chains and then increased the average viscosity molecular weight for material (PVA) that used in this research. Keywords: Health, gamma rays, Distilled water.